2010
DOI: 10.1590/s1413-70542010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da temperatura de secagem na qualidade de grãos de aveia branca

Abstract: RESUMOObjetivou-se, com o trabalho, avaliar o efeito de diferentes temperaturas do ar de secagem na qualidade física, química e biológica de grãos de aveia branca da cultivar Albasul. Grãos de aveia (Avena sativa L.) foram submetidos à secagem estacionária com temperaturas de 25, 50, 75 e 100 ºC até a umidade de 13 %, em delineamento inteiramente casualizado. Nas amostras, foram determinados peso volumétrico, peso de 1000 grãos, germinação e vigor. Os grãos de aveia foram submetidos ao descascamento, moagem em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
4
5
0
3
Order By: Relevance
“…These results agree with those obtained by Eichelberger & Portella (2003) and Oliveira et al (2010), which studied the drying of corn and oat grains. They found that increasing the drying temperature resulted in the reduction of the 1,000-seed weight and hectoliter weight of the grains.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with those obtained by Eichelberger & Portella (2003) and Oliveira et al (2010), which studied the drying of corn and oat grains. They found that increasing the drying temperature resulted in the reduction of the 1,000-seed weight and hectoliter weight of the grains.…”
Section: Resultssupporting
confidence: 93%
“…Some studies have addressed the effects of drying temperature on the physical and physiological quality of oat seeds, adzuki bean and sorghum (Oliveira et al 2010, Ullmann et al 2015. In relation to beans, Afonso Júnior & Corrêa (2000) and Faroni et al (2006) studied the effects of different drying temperatures on the physical and physiological quality of seeds and bean grains, respectively, harvested with different moisture contents.…”
Section: Palavras-chavementioning
confidence: 99%
“…ISSN 2166-0379 2020 There was no direct relationship between the protein content and the drying conditions used, which also did not influence the lipid content. Similar behavior was reported by Oliveira et al (2010) for white oat grains submitted to drying at different temperatures (50, 75 and 100 °C), with no significant statistical changes in the lipid content found.…”
Section: Characterization Of the In Nature And Germinated Jackfruit Ssupporting
confidence: 87%
“…The use of high temperatures in drying can compromise the physical and chemical characteristics of grains, causing oil darkening, protein denaturation and starch gelatinization. Evaluating starch content in white oat with drying temperature of 25, 50, 75 and 100 ºC, it was found a reduction in starch content with increased drying temperature (OLIVEIRA et al, 2010). The reduction of starch and soluble dietary fiber can be explained by the use of high temperatures that lead to the complexation of these compounds (GUTKOSKI et al, 2000;LAMMENS et al, 2012;BROWN et al, 2013).…”
Section: Resultsmentioning
confidence: 99%